PROVIDING EDUCATION ABOUT POSTPARTUM BLUES - Ruspita, Rika; Susanti, Komaria; Rahmi, Rifa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Puerperal services are standard health services for mothers from 6 hours to 42 days after delivery by health workers. The service is carried out in the puerperal period because it is a time of crisis for both the mother and the baby. The prevalence of postpartum blues events varies worldwide. The prevalence of postpartum blues in Tanzania is 80% while in Japan it is 8%. This is due to the lack of different diagnosis criteria and research methodologies in each study, in Asia, the prevalence of postpartum depression is between 3.5%- 63.3% where Malaysia and Pakistan rank the lowest and highest. The purpose of this devotion is to improve the mother's understanding of postpartum blues. The solution to the problems faced by the community, especially postpartum mothers, is by providing counseling about postpartum blues. The targeted output of this community service activity is an increase in the understanding of postpartum blues